Why, what, who and when: an overview of the Cassava Biotechnology Network (CBN) and current cassava biotechnology research worldwide - Thro, Ann Marie; Bonierbale, Merideth W.; Roca, W.; Best, R.; Henry, Guy (International Center for Tropical Agriculture, 1995)
CBN is an informal forum for cassava biotechnologists, collaborating research and development specialists, and cassava research users. CBN`s research goals are genetic and processing improvements for cassava. Its development goal is to encourage interdisciplinary research in national programs of cassava- growing countries, in projects appropriate to improving national food security and contributing to rural income. To foster development of biotechnology as a tool for cassava improvement, CBN coordinates assessments of research needs; promotes collaborative research on topics identified as priority; and facilitates exchange of information on research needs and activities. Cassava biotechnology research is conducted in 25 cassava- growing countries, 13 additional countries, and two international centers. There are approximately 120 cassava biotechnology research projects currently being carried out world- wide. Mature technologies, already in widespread use, include cassava micropropagation and cassava microbial technologies; these account for almost half of the existing projects. The first molecular markers for important cassava traits are expected to be ready for plant breeding programs in 2 to 4 years, as are the first experimental products of cassava genetic transformation and gene cloning. A molecular genetic map of cassava is available for use this year. This biotech tools can be used by researchers to create new opportunities for cassava farmers and processors, as well as to solve specific problems in cassava production, processing, and marketing